Дослідження механізмів управління фінансовими ресурсами будівельних підприємств - Коваленко, Є. С. (Ways to Improve Construction Efficiency, 2013)
Proposed scientific and methodical approach to the study of the economic mechanism of financial management of construction enterprises. The basis of the approach is the correlation and regression analysis of the dynamics of economic development construction companies. The developed approach, the dependence of the cash flows of construction companies on the intensity of attraction and use of financial resources.